Effects of live yeast and starch supplementation on in vitro fermentation and methane production of tropical grass - Elder Cavalcante Fabian; Bruno Carneiro e Pedreira; Ana Cláudia da Costa; Nelcino Francisco de Paula; Alessandra Schaphauser Rosseto Fonseca; Karine Padilha Nunes Vieira; Rodrigo Dias Lauritano Pacheco; José Roberto Tavares; Farah Arruda Petter; Fagton de Mattos Negrão; Luciano da Silva Cabral (Scientia Agricola)
ABSTRACT This study aimed to evaluate the effects of supplementation of live yeast (LY) associated with starch levels (SL) on the in vitro kinetic parameters of the gas production (GP), in vitro neutral detergent fiber digestibility (IVNDFD), volatile fatty acid (VFA) and methane (CH4) production of Urochloa brizantha cv. Marandu grass harvested in both the rainy and dry seasons. The study was conducted in a 2 × 3 factorial arrangement, whereby LY supplementation (with and without LY) was associated with 0, 10, and 20 % of starch supplementation. The variables were analyzed using PROC MIXED in SAS (Statistical Analysis System, version 9.3). LY and SL had no interaction effects on any of the variables tested. LY supplementation increased total GP at 72 h of incubation in both forage seasons by approximately 25 %. Additionally, LY supplementation decreased lag time; however, the GP rate was unaffected. The LY also caused a slight drop in IVNDFD at 48 h in both forage seasons. LY supplementation decreased total VFA production by 25.96 % for the rainy season and 11.32 % for the dry season and caused a 40 and 46 % drop in CH4 for the rainy and dry season forage, respectively. The assumption that combining LY and starch would enhance LY activity was not confirmed in this study, as most analyzed variables showed no interaction between the two factors. Consequently, no beneficial effects on increased SL could be attributed to LY supplementation.